Moderna knjižnica v stiku z otroki - Mersich, Brigitte (Knjižnica, 2004)
Recently an increasing number of children comes to scientific libraries, not for scientific research of course, but as visitors: they take part in guided tours or workshops, visit exibitions or celebrate their birthdays in the rooms of the library. Therefore special educational programmes should be focusing on this important group of visitors more and more. The author makes some suggestions on how to develop a tailored concept to address the group of young customers.
Keywords: znanstvene knjižnice; izobraževalni programi; otroci; child; Austria; Avstrija